DIAGNÓSTICO DIFERENCIAL ENTRE A RAIVA E A CINOMOSE CANINA EM AMOSTRAS DE CÉREBRO DE CÃES EXAMINADAS NO PERÍODO DE 1998 A 2001 NA REGIÃO DE ARAÇATUBA, SP, BRASIL - Silva, L.h. Queiroz Da [UNESP]; Morinishi, C.k. [UNESP]; Nunes, C.m. [UNESP] (Instituto Biológico, 2024)
Human rabies control could not be achieved without rabies control in dogs and the dog rabies surveillance is one of the most important measures for this goal. Some neurological symptoms of canine distemper are similar to rabies and usually they are sent for examination to rabies laboratories. A total of 1,866 canine central nervous system fragment received by the Rabies Laboratory of UNESP/Araçatuba, SP, from 1998 to 2001, were evaluated for rabies diagnosis, and 248 negative samples were submitted to differential diagnosis for canine distemper by the fluorescent antibody test. Positive results were observed in 18.9% (47/248) of the samples and virus antigen was detected by fluorescent antibodies uniformly in all the central nervous system areas examined (cerebral cortex, cerebellum and hippocampus), therefore, the evaluation of any fragment will be useful for the diagnosis of canine distemper.

O controle da raiva humana depende do controle da raiva, principalmente, em áreas urbanas, fazendo-se necessário implementar a vigilância epidemiológica da raiva canina. Em cães, uma das enfermidades que resulta em sintomatologia nervosa, como incoordenação motora, convulsões e ataxia, é a cinomose, a qual pode ser confundida com a raiva. No período de 1998 a 2001 o Laboratório de Raiva da UNESP/Araçatuba avaliou 1.866 amostras de sistema nervoso central (SNC) de cães, para diagnóstico de raiva. Destas, 248 amostras que apresentaram resultado negativo para raiva e eram provenientes de animais que apresentaram alterações do SNC foram analisadas pela técnica da imunofluorescência direta (IFD) para diagnóstico diferencial com cinomose. Resultados positivos foram observados em 18,9% (47/248) das amostras, sendo que os antígenos virais foram detectados uniformemente em todas as porções analisadas do sistema nervoso central (córtex, cerebelo e hipocampo), não tendo sido observada correlação estatística na localização preferencial do vírus.
DIFFERENTIAL DIAGNOSIS BETWEEN RABIES AND CANINE DISTEMPER IN CENTRAL NERVOUS SYSTEM SAMPLES FROM 1998 TO 2001 IN ARAÇATUBA REGION, SP, BRAZIL
Keywords: Dog rabies; canine distemper disease; diagnosis; fluorescent antibody test.; Raiva canina; cinomose; diagnóstico diferencial; imunofluorescência direta.